Generalized Schultz and Modified Schultz Polynomials for Some Special Graphs - Najm, Esraa A.; Ali, Ahmed M. (Iraqi Journal of Science, 2024)
With simple and undirected connected graph Φ, the Schultz and modified Schultz polynomials are defined as and , respectively, where the summation is taken over all unordered pairs of distinct vertices in V(Φ), where V(Φ) is the vertex set of Φ, degu is the degree of vertex u and d(v,u) is the ordinary distance between v and u, u≠v. In this study, the Shultz distance, modified Schultz distance, the polynomial, index, and average for both have been generalized, and this generalization has been applied to some special graphs.